2020
DOI: 10.1021/acs.langmuir.0c02832
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Study of Bubble Nucleation on an Ideally Smooth Substrate

Abstract: Questions regarding bubble nucleation on an ideally smooth surface are seemingly endless, but it can not be adequately verified yet because of the scale limitation (microscopic scale). Hence, in this study, bubble nucleation on an ideally smooth substrate is explored using the molecular dynamics simulation method. An ideally smooth hydrophilic platinum substrate at 145 K is conducted to heat the simple L–J liquid argon. Results show that a visible bubble nucleus successfully forms on the ideally smooth substra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Figure shows that bubble nuclei first originate at the base corner of nanopillars on the surface R o . To analyze the behaviors of bubble nucleation, we computed the potential energy , U of one single water molecule at the solid–liquid interface. Taking the surface R o for example, as shown in Figure b, we chose a structural unit (one single pillar) and calculated the potential energy between one single water molecule and all solid atoms according to the 12-6 LJ potential function.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure shows that bubble nuclei first originate at the base corner of nanopillars on the surface R o . To analyze the behaviors of bubble nucleation, we computed the potential energy , U of one single water molecule at the solid–liquid interface. Taking the surface R o for example, as shown in Figure b, we chose a structural unit (one single pillar) and calculated the potential energy between one single water molecule and all solid atoms according to the 12-6 LJ potential function.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike traditional computational fluid dynamics simulations, the MD method can directly explore the nanoscopic origins, elucidate phenomena from a molecular perspective, and provide a fundamental understanding that is not accessible by experiments; thus, it has been widely used to investigate various interfacial phenomena, such as droplet wetting, , impact, coalescence, , and evaporation, , as well as liquid boiling and vapor condensation. , In this paper, nonequilibrium molecular dynamics simulations were performed to investigate the nanoscale thin-film boiling process. Aiming at understanding the initial bubble behaviors and the heat and mass transfer performance, this work was conducted and illustrated around the following objectives: (1) capturing the triple-phase interface to record the lifetime of nanobubbles, (2) visualizing the internal fluid flow and thermal characteristics, (3) studying the effects of surface physicochemical properties on boiling performance, and (4) revealing the essential regulation mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Due to strong solid–fluid wettability, nanobubbles do not originate from the solid surface and there is a nonevaporation ultrathin film covering in the solid surface, which is also observed in other studies. , To further understand this, the potential energy contour of fluid is calculated (see Figure ). From energy point of view, , low potential energy means large energy barrier for evaporation or boiling and only when liquid overcomes their potential barrier can the bubble nucleus form. As can be seen in Figure , fluid close to the solid surface owes much low potential energy, which strongly impedes the evaporation and boiling.…”
Section: Resultsmentioning
confidence: 99%
“…33,34 To further understand this, the potential energy contour of fluid is calculated (see Figure 7). From energy point of view, 35,36 low potential energy means large energy barrier for evaporation or boiling and only when liquid overcomes their potential barrier can the bubble nucleus form. As can be seen in Figure 7, fluid close to the solid surface owes much low potential energy, which strongly impedes the evaporation and boiling.…”
Section: ■ Computational Methodsmentioning
confidence: 99%
“…Though similar studies on evaporation of water or different aqueous films can be found in the literature, significantly less research has been done in understanding the film boiling and at the molecular level in the presence of an electric field. Similarly, molecular-level study of nucleate boiling on smooth surfaces, on surfaces with cavities, and on surfaces with varying wettabilities can be seen in the literature, but the effect of an electric field is yet to be explored. Hence, in the present paper, molecular dynamics simulations have been performed in an attempt to understand and control film and nucleate boiling using an electric field.…”
Section: Introductionmentioning
confidence: 99%